Dampak Regulasi Obat-obat Tertentu terhadap Respon Industri Farmasi di Indonesia - Ernawati, Diana; Munira, Syarifah Liza (Jurnal Kebijakan Ekonomi, 2020)
This study analyzes the impact of the regulation of Spesific Drugs (OOT) applied to pharmaceutical companies producing OOT in 2018 on the number of OOT production. Using the difference-in-differences (DID) approach method, this study looked at the influence of the 5 (five) OOT groups. The results of this study indicate that there has been a decrease in the amount of OOT production which is also influenced by regulations, an increase in the price of medicinal raw materials (active drug ingredients), and the setting of finished drug prices. The variables that affect decreasing production are the generic drug class for the tablet form of drugs, in multi-product companies with the status of state-owned companies (BUMN). The comparison between the level of production and the need for drugs in the year before the enactment of the regulation shows that the amount of production is still above the need and after the regulation, the amount of production is below the amount needed. This will have an impact on the availability and price of OOT in health care facilities. These results underline that regulations in the pharmaceutical sector will have an impact, one of which on the decisions of manufacturers in determining the amount of drug production.